2018
DOI: 10.1002/app.46309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disulfide chain extender effect on the mechanical properties of unsaturated polyurethane‐urea networks

Abstract: 4-Aminophenyl disulfide and bis(4-aminophenyl)methane chain extenders containing hydroxyl-terminated polybutadienebased polyurethane-ureas are prepared one-shot to explore the effect of the chain extender structure on the elastomers mechanical properties. However, the results revealed that the participation of the disulfide chain extender in side reactions like thiol-ene and proton abstraction prevented disulfide metathesis reaction due to decomposing chain extender in the polyurethane-urea matrix. Also, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…20,30 The dynamic behaviour of the aromatic disulfide at reduced temperatures has subsequently been explored by several groups in the area of self-healing. [31][32][33] For example, using the same disulfide Yang et al synthesized a PU elastomer with improved tensile strength for which self-healing could be induced by heating to 60 °C. They observed that for more cross-linked materials a higher tensile strength was obtained, but this occurred with a concomitant lowering of the ability to self-heal.…”
Section: Introductionmentioning
confidence: 99%
“…20,30 The dynamic behaviour of the aromatic disulfide at reduced temperatures has subsequently been explored by several groups in the area of self-healing. [31][32][33] For example, using the same disulfide Yang et al synthesized a PU elastomer with improved tensile strength for which self-healing could be induced by heating to 60 °C. They observed that for more cross-linked materials a higher tensile strength was obtained, but this occurred with a concomitant lowering of the ability to self-heal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the radical cleavage of the S-S bonds during raising temperature decreased the mechanical strength of the EP-DTPA samples. 41 Moreover, the performed metathesis reaction in these samples could be followed up in tan δ curve, too. The loss modulus enhancement by introducing of the DTPA in EP-DTPA samples was initiated from about 5 C. As a consequence, it was expected that the healing process for the prepared coatings initiated from upper temperature than room temperatures.…”
Section: Atr-ir Spectroscopymentioning
confidence: 99%
“…38 Considerably, the fabricated elastomer via their suggested method could be reshaped and reprocessed by room-temperature compression through rearrangements of the cross-linked. 38 In continuous to our previous studies on self-healing materials [39][40][41][42][43] and polymer properties, 25,44 self-heal epoxy coatings have been prepared using disulfide metathesis reaction. In this regard, an epoxy terminated chain extender with capability of performing reversible reaction has been synthesized via functionalization of 3,3 0 -dithiodipropionic acid (DTPA) with bisphenol A diglycidyl ether (DGEBA).…”
Section: Introductionmentioning
confidence: 99%
“…The chain extender is an available additive to solve this problem, but it cannot inhibit the dewetting, which may influence its effect on the contrary [21]. Abd Elall [1] used fatty monocarboxylic acid and dicarboxylic acid with methyl aziridinyl phosphine oxide (MAPO) to form (MSA) bonding agent which improved the mechanical properties especially strain value corresponding to stress value.…”
Section: Introductionmentioning
confidence: 99%